The genus Peckia Robineau-Desvoidy (Diptera: Sarcophagidae) in the Brazilian Amazon: a new species, new records, descriptions of female terminalia and key to species - de Camargo, Sofia Lins Leal Xavier; Carvalho-Filho, Fernando Da Silva; Esposito, Maria Cristina (Zootaxa, 2018)
Flesh flies of the genus Peckia Robineau-Desvoidy, 1830 were studied from the Brazilian Amazon region. The male terminalia of all species are illustrated. The female terminalia are described and illustrated for all species for which the female is known. The female terminalia of six species are described for the first time; those of seven species are redescribed and documented through new illustrations. A new species of the subgenus Pattonella Enderlein, 1928, Peckia (Pattonella) juruti sp. nov., is described. It is similar to Peckia (Pattonella) smarti (Lopes, 1941) in the shape of the cercus and distiphallus, but differs in the shape of the gonites, juxta and capitis. Peckia (Peckia) hillifera (Aldrich, 1916) is recorded from Brazil for the first time; Peckia (Euboettcheria) florencioi (Prado & Fonseca, 1932) is newly reported for the Brazilian Amazon. A key to the 21 species of Peckia so far recorded from the Brazilian Amazon is provided, allowing the identification of both sexes where known. The females of only five of these species remain unknown.